Integration of Horde Email System and Mobile Application System - Sofiah, Othman (2010)
Using technology as a communication tool within an organization can improve the communication process and make the communication process within an organization becomes easier. The aim of this research is to develop system integration between mobile application and email system to enhance the communication process in an organization. To develop this integration system, some researches have to be done in order to get all requirements need and to assist in system development. The result obtained from this study hopefully can be applied and the development of the system will be continued to build an integrated system using email and mobile application service.